Pelatihan Pengentasan Buta Huruf Al-Qur’an melalui Model Pembelajaran LITERAT bagi Guru di Kabupaten Bandung: Training for Al-Qur’an Literacy Enhancement through the LITERAT Learning Model for Teachers in Bandung Regency - Supriadi, Udin; Faqihuddin, Achmad; Tantowi, Yusuf Ali; Subakti, Ganjar Eka; Islamy, Mohammad Rindu Fajar (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Qur’anic Literacy Eradication Training through the LITERAT Learning Model aims to enhance the capacity of Islamic Education (PAI) teachers in systematically assessing and teaching Qur’anic literacy. The training involved 50 teachers in Bandung Regency and was conducted as an interactive workshop combining theoretical presentations, simulations, and hands-on practice. The LITERAT model—which consists of seven stages: Listening, Identification, Treatment, Explanation, Reading, Assessment, and Testing—equips participants with the ability to categorize students’ Qur’anic reading skills into five levels: TPD1, TPD2, TD, TT, and TM. Before the training, most participants could only make general distinctions between "fluent" and "non-fluent" students in reading the Qur’an. After completing the training, participants reported the ability to apply classification indicators in a more measurable and structured manner. Pre-test results showed an average participant score of 61.5, which increased to 83.2 in the post-test. The majority of participants demonstrated improvement in the accuracy of student assessment classifications. Additionally, the majority of participants stated that the training was highly beneficial. The training strengthened participants’ understanding of the LITERAT model and improved their pedagogical and evaluative competencies in Qur’anic instruction. This intervention significantly contributes to empowering teachers as objective, data-driven evaluators of religious literacy.